Retrospective Study Looking at Cinacalcet in the Management of Hyperparathyroidism after Kidney Transplantation - Habib Mawad; Hugues Bouchard; Duy Tran; Denis Ouimet; Jean-Philippe Lafrance; Robert Zoël Bell; Sarah Bezzaoucha; Anne Boucher; Suzon Collette; Vincent Pichette; Lynne Senécal; Michel Vallée (Journal of Transplantation)
Objectives. The primary objective of this study is to evaluate the use of cinacalcet in the management of hyperparathyroidism in kidney transplant recipients. The secondary objective is to identify baseline factors that predict cinacalcet use after transplantation. Methods. In this single-center retrospective study, we conducted a chart review of all patients having been transplanted from 2003 to 2012 and having received cinacalcet up to kidney transplantation and/or thereafter. Results. Twenty-seven patients were included with a mean follow-up of 2.9±2.4 years. Twenty-one were already taking cinacalcet at the time of transplantation. Cinacalcet was stopped within the first month in 12 of these patients of which 7 had to restart therapy. The main reason for restarting cinacalcet was hypercalcemia. Length of treatment was 23±26 months. There were only 3 cases of mild hypocalcemia. There was no statistically significant association between baseline factors and cinacalcet status a year later. Conclusions. Discontinuing cinacalcet within the first month of kidney transplantation often leads to hypercalcemia. Cinacalcet appears to be an effective treatment of hypercalcemic hyperparathyroidism in kidney transplant recipients. Further studies are needed to evaluate safety and long-term benefits.